KIR2DL5: An Orphan Inhibitory Receptor Displaying Complex Patterns of Polymorphism and Expression - Cisneros, Elisa; Moraru, Manuela; Gómez-Lozano, Natalia; López-Botet, Miguel; Vilches, Carlos (Frontiers in Immunology, 2012)
A recently developed anti-KIR2DL5 (CD158f) antibody has demonstrated KIR2DL5 expression on the surface of NK and T lymphocytes, making it the last functional KIR identified in the human genome. KIR2DL5 belongs to an ancestral lineage of KIR with Ig-like domains of the D0-D2 type, of which KIR2DL4, an HLA-G receptor, is the only other human member. Despite KIR2DL4 and KIR2DL5 being encoded by genes with similar domain usage, several KIR2DL5 functions resemble more closely those of KIR recognising classical HLA class I molecules – surface-expressed KIR2DL5 inhibits NK cells through the SHP-2 phosphatase and displays a clonal distribution on NK and T lymphocytes. No activating homologue of KIR2DL5 has been described in any species. The genetics of KIR2DL5 is complicated by duplication of its gene in an ancestor of modern humans living ~1.7 million years ago. Both KIR2DL5 paralogues have undergone allelic diversification; the centromeric gene is most often represented by alleles whose expression is silenced epigenetically through DNA methylation, thus providing a natural system to investigate the regulation of KIR transcription. The role of KIR2DL5 in immunity is not completely understood, in spite of different attempts to define its ligand. Here we revisit the most relevant characteristics of KIR2DL5, an NK-cell receptor possessing a unique combination of genetic, structural and functional features.